TECHNIKI OBRAZOWANIASingle round shadow of the lung: carcinoma or round pneumonia? – diagnostic problem, differential diagnosis - Halkiewicz, Franciszek; Kozielski, Jerzy; Witkowska-Klinke, Joanna; Kluczewska, Ewa; Głowacki, Jan; Machura, Edyta (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Round shadow in the radiological images of the lungs is an important symptom of various diseases including pulmonary neoplasms. In the paper there is described a patient with pneumonia with radiological features of a round shadow suggesting tumor. The differential diagnostics of the single round shadow of the lung are described including inflammatory changes.